(untitled) (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2025)
Previous studies have emphasized the ecological benefits of shaded agroecosystems in enhancing arthropod diversity and maintaining ecosystem stability, yet limited research has focused on Momordica charantia under such conditions. This study aimed to assess the diversity and abundance of arthropods inhabiting bitter melon plants grown beneath shade. The research was conducted for five consecutive weeks using direct observation and trapping methods in a field setting, with specimens identified to the morphospecies level and classified by ecological role. A total of 465 individuals were recorded, consisting of pollinators, detritivores, pests, and predators. The Shannon–Wiener diversity index (H’) indicated moderate diversity, and the evenness index (E) showed high community uniformity, reflecting ecological stability. Pollinators and detritivores were the most dominant functional groups, while pests and predators appeared in low abundance, suggesting natural regulatory interactions. These findings demonstrate that shaded bitter melon ecosystems can sustain high arthropod diversity and provide essential ecosystem services such as pollination and biological control, supporting sustainable agroecosystem management.